APLIKASI LAPORAN KEBERANGKATAN DAN KEDATANGAN ALAT ANGKUT KANTOR IMIGRASI JAMBI: Application;Transport Equipment;Immigration Office;PHP;HTML. - Puad, Lailyn; Limia Budiarti, Rike; Gloria Lbn.Tobing, Delvi (JURNAL AKADEMIKA, 2022)
Information System Application Reporting Departure and Arrival of Transport Equipment of the Jambi Immigration Office is a system of convenience in making reports on recording ship departures and ship arrivals at ports from things such as data recap, report entry and also ease of inspection on ships dating and departing. From where in building the system in this system development tools are used, namely Data Flow Diagrams (DFD) and Context Diagrams, as well as using the PHP and HTML programming languages ​​and MySQL as databases.